2011
DOI: 10.1080/02786826.2010.524680
|View full text |Cite
|
Sign up to set email alerts
|

Size Distributions of Polycyclic Aromatic Hydrocarbons at Two Receptor Sites in the Pearl River Delta Region, China: Implications of a Dominant Droplet Mode

Abstract: . The less volatile five-to six-ring PAHs were mainly distributed in the condensation mode and droplet mode, with little presence in the coarse mode. The droplet mode was the most prominent mode for all PAHs at both sites, accounting for more than 70% of the total particle-phase five-and six-ring PAHs and more than 60% of the total particle-phase three-and four-ring PAHs. The dominant droplet mode could be attributed to a result of in-cloud processing of vehicular soot particles and biomass burning particles d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The meteorological data that drove the model were from the Global Data Assimilation System (GDAS) data set (3 hourly, global, 1 • in longitude and latitude, and 23 pressure levels). For each sampling day, 10-h backward [31] and several biomass burning in dilution chamber measurements [32]. The coal combustion profiles are selected from coal combustion in the main coal-mining regions in China [19].…”
Section: Impact Of Inland and Outland Prdmentioning
confidence: 99%
See 2 more Smart Citations
“…The meteorological data that drove the model were from the Global Data Assimilation System (GDAS) data set (3 hourly, global, 1 • in longitude and latitude, and 23 pressure levels). For each sampling day, 10-h backward [31] and several biomass burning in dilution chamber measurements [32]. The coal combustion profiles are selected from coal combustion in the main coal-mining regions in China [19].…”
Section: Impact Of Inland and Outland Prdmentioning
confidence: 99%
“…Also plotted in Fig. 5 are ratio ranges obtained from source profiles measured in other studies [19,[30][31][32]. It is practical to select source profiles that could represent local emissions.…”
Section: Source Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 to visualize the measured ambient PAH data in this study and PAH data previously reported for another two locations in urban Guangzhou (Li et al, 2006;Yang et al, 2010). Also shown are published source profiles for vehicle emissions, biomass burning and coal combustion (He et al, 2008;Sheesley et al, 2003;Yu and Yu, 2011;Zhang et al, 2008). The vehicle emission composition is from data collected in Zhujiang Tunnel in the western urban area of Guangzhou (He et al, 2008).…”
Section: Source Identification Of Pahsmentioning
confidence: 99%
“…The vehicle emission composition is from data collected in Zhujiang Tunnel in the western urban area of Guangzhou (He et al, 2008). The biomass burning profiles are measured data of rice straw burning emissions obtained in open field burning in the PRD (Yu and Yu, 2011) and in dilution chamber measurements (Sheesley et al, 2003) and sugarcane burning in the PRD (Yu and Yu, 2011). The coal combustion profiles are selected from industrial coal combustion with coal from the main coal-mining regions in China .…”
Section: Source Identification Of Pahsmentioning
confidence: 99%